Naturalizing Disaster in Media Discourse: A Critical Discourse Analysis of the Sibolga Landslide Coverage on Kompas TV - Dwi Angeli Pardede; Isabel Selmiola Sabrina; Bella Sonia Sianturi; Partohap Saut Raja Sihombing (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Disaster discourse in Indonesian media often emphasizes natural factors while marginalizing structural causes, thereby depoliticizing complex socio-environmental issues. This study investigates the discursive construction of the Sibolga landslide as represented in the Kompas TV news article "PVMBG Ungkap Penyebab Longsor di Sibolga: Lereng Curam dan Hujan Ekstrem" published on November 27, 2025. Adopting a descriptive qualitative design within a critical paradigm, the research employs Norman Fairclough's three-dimensional Critical Discourse Analysis framework, encompassing textual features, discursive practices, and socio-cultural contexts. The analysis reveals that the news discourse predominantly naturalizes the disaster by foregrounding geological and meteorological explanations provided by PVMBG, while systematically excluding perspectives from affected communities, independent researchers, and environmental advocates. Linguistic choices and narrative strategies legitimize scientific-institutional authority as the sole source of truth, while structural factors such as spatial planning violations, deforestation, and governance failures receive minimal or no attention. The study demonstrates how news media function not merely as information channels but as ideological spaces that reproduce dominant discourses on disaster, shifting responsibility from human actors and policies to uncontrollable natural forces. This research contributes to critical media and disaster studies by exposing how naturalization discourse reduces public demand for structural reforms and perpetuates vulnerability in disaster-prone communities in Indonesia.